The language of canon law - Hahn, Judith (Oxford studies in language and law, 2023)
"This study explores the language of canon law, the legal order of the Roman Catholic Church. It seeks to bring the language of canon law into the law and language debate and in doing so better understand how the Roman Catholic Church communicates as a legal institution. It ex-amines the function of canon law language in ecclesiastical communications. It studies the character of canonical language, the grammar and terminology of canon law, and how it makes use of linguistic tricks and techniques to create its typical sound. It discusses the com-prehension difficulties that arise out of ambiguities in the law, out of transfer problems be-tween legal and common language, and out of canon law's confusing mix of legal, doctrinal, and moral norms. It reviews the potential consequences of a plain language agenda in the church. This includes an evaluation of whether dead Latin is the appropriate language for a global and cross-cultural legal order such as canon law, and a discussion of how to improve multi-language communication. It takes a closer look at ecclesiastical interpretation theory. It examines forensic language, the language of ecclesiastical tribunals, in its problematic shifting between orality and textuality"--